Pornographic Media, Parental Roles, and Adolescent Sexuality - Imanah Rahmawati; Fenny Etrawati; Lisa Agustina (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Access to pornography among adolescents can inflict various threats such as pornography addiction, risky sexual behaviour, Sexually Transmitted Diseases (STDs), unplanned pregnancies, and illegal abortions. Thus, this study aimed to identify exposure to pornographic media and the role of parents in adolescent sexual behaviour. This study used a qualitative approach with a purposive sampling technique to select informants, including 12 adolescents as key informants, 12 parents and 4 teachers as expert key informants. Data were collected using 2 methods: in-depth interviews with expert key informants and Focus Group Discussions (FGD) with adolescents as key informants. The data were analyzed using thematic analysis technique. The data validity, were assessed using a triangulation method, mainly the source, method, and data itself. This study found that low self-control in adolescents drives them to engage in risky sexual behaviour, such as holding hands, kissing, and touching their partner's sensitive areas. Exposure to pornography encouraged them to imitate the acts in such videos, ranging from masturbation to sexual stimulation of a partner. Lack of reproductive health information and parental supervision often makes adolescents make sexual decisions without careful consideration. Providing comprehensive sex education accompanied by parental supervision can be a preventive effort against deviant sexual behaviour among adolescents.